A Comparative Study between Preoperative Computed Tomography and Intraoperative Ossicular Chain Status in Patients of Chronic Suppurative Otitis Media at RIMS, Ranchi - Nishant Abhishek Kujur; Binod Kumar Sinha; Indira Margret Murmu; Karmbir; Manuwel Tudu; Rajeev Kumar Ranjan (Journal of Pharmacy and Bioallied Sciences)
Background: Chronic suppurative otitis media (CSOM) is a persistent middle ear infection often leading to conductive hearing loss due to ossicular chain damage. Accurate preoperative assessment using high-resolution computed tomography (HRCT) is crucial for surgical planning. This study compares preoperative HRCT findings with intraoperative ossicular chain status in CSOM patients. Aims and Objectives: To evaluate the correlation between preoperative computed tomography scans and intraoperative ossicular chain status in CSOM patients. Methodology: The study included 60 CSOM patients aged 12 to 60 years attending the ENT department at Rajendra Institute of Medical Sciences, Ranchi. Preoperative HRCT was performed, and intraoperative findings were compared. Data analysis was conducted using SPSS version 17.0. Results: Ossicular erosion was observed in 61.7% of cases, predominantly affecting the incus. HRCT showed high sensitivity and specificity in detecting ossicular chain damage, aligning with intraoperative findings. Conclusion: HRCT provides valuable preoperative insights but should complement intraoperative assessment. Combining both approaches ensures accurate diagnosis and effective management of CSOM.